Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pengusaha UMKM Coffee Shop Di Kecamatan Buduran Kabupaten Sidoarjo - M. Rizky Dimas Ramadhan; Muhammad Yasin (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
The Coffee Shop business is one of the businesses that are in great demand by business people in the Buduran District. Starting a Coffee Shop business, the capital aspect is a very important thing to consider. To increase the product sold a business has to purchase a large quantity of merchandise. The focus of this research is (1) Does working capital, labor, and working hours simultaneously affect the income of UMKM Coffeeshop entrepreneurs in Buduran District (2) Does working capital, workforce, and working hours have a significant effect on the income of Coffeeshop entrepreneurs in Buduran District. The method used in this study is a quantitative method that aims to test theories, build facts, and show relationships between variables. The feasibility analysis used is multiple linear regression, F-test, and t-test. The results of this study with the help of SPSS data processing software produce capital, labor, and working hours variables that have a positive value on income in linear regression analysis. However, there are some suggestions that need to be considered and have been conveyed by the author in conducting this research. Because these suggestions are constructive suggestions to continue to increase Coffeeshop business income which is run by entrepreneurs.